Retinal glutamate neurotransmission: from physiology to pathophysiological mechanisms of retinal ganglion cell degeneration - Boccuni, Isabella; Fairless, Richard (Life, 2022)
Glutamate neurotransmission and metabolism are finely modulated by the retinal network, where the efficient processing of visual information is shaped by the differential distribution and composition of glutamate receptors and transporters. However, disturbances in glutamate homeostasis can result in glutamate excitotoxicity, a major initiating factor of common neurodegenerative diseases. Within the retina, glutamate excitotoxicity can impair visual transmission by initiating degeneration of neuronal populations, including retinal ganglion cells (RGCs). The vulnerability of RGCs is observed not just as a result of retinal diseases but has also been ascribed to other common neurodegenerative and peripheral diseases. In this review, we describe the vulnerability of RGCs to glutamate excitotoxicity and the contribution of different glutamate receptors and transporters to this. In particular, we focus on the N-methyl-d-aspartate (NMDA) receptor as the major effector of glutamate-induced mechanisms of neurodegeneration, including impairment of calcium homeostasis, changes in gene expression and signalling, and mitochondrial dysfunction, as well as the role of endoplasmic reticular stress. Due to recent developments in the search for modulators of NMDA receptor signalling, novel neuroprotective strategies may be on the horizon.
Gesehen am 07.07.2022
This article belongs to the special issue "New insights on cellular biology of retinal degenerations"